2015
DOI: 10.3126/njst.v15i2.12122
|View full text |Cite
|
Sign up to set email alerts
|

Nalidixic Acid Susceptibility Test for Screening Salmonella Isolates of Reduced Susceptibility/Higher Minimum Inhibitory Concentration to Ciprofloxacin

Abstract: Enteric fever is the major diagnosis among febrile patients in Nepal with yearly increase in nalidixic acid resistance and reduced ciprofloxacin susceptibility among Salmonella isolates. This study was carried out to evaluate the validity of nalidixic acid resistance as an indicator of reduced susceptibility of Salmonella isolates to ciprofloxacin. In this study, 999 blood specimens collected from suspected enteric fever patients visiting B&B Hospital were processed by standard microbiological techniques. Isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The rate of nalidixic acid resistance was observed as high (72.7%) but somewhat similar to the result demonstrated by Acharya et al (80%) and Shrestha et al (83.1%) [ 11 , 24 ]. NARS strains have reduced fluoroquinolone susceptibility and nalidixic acid resistance has been used as an indirect indicator of increased minimum inhibitory concentration for ciprofloxacin [ 25 ]. Even Acharya et al from Nepal demonstrated the decrease in ciprofloxacin susceptibility (MICs 0.125–0.5 mg/L) among the NARS strains [ 24 ], whilst this study strongly nullifies the use of nalidixic acid as surrogate marker of ciprofloxacin susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of nalidixic acid resistance was observed as high (72.7%) but somewhat similar to the result demonstrated by Acharya et al (80%) and Shrestha et al (83.1%) [ 11 , 24 ]. NARS strains have reduced fluoroquinolone susceptibility and nalidixic acid resistance has been used as an indirect indicator of increased minimum inhibitory concentration for ciprofloxacin [ 25 ]. Even Acharya et al from Nepal demonstrated the decrease in ciprofloxacin susceptibility (MICs 0.125–0.5 mg/L) among the NARS strains [ 24 ], whilst this study strongly nullifies the use of nalidixic acid as surrogate marker of ciprofloxacin susceptibility.…”
Section: Discussionmentioning
confidence: 99%